Regiony absorpcji i generowania impulsów innowacyjnych - studium przykładu regionów południowych w Polsce - Broszkiewicz, Ryszard; Pokusa, Tadeusz (The Regions of Absorption and Generating the Innovation Impulses - The Example of South Regions in Poland, 2008)
The statistical analysis of the research process was focused on the following regions: lubuski, dolnośląski, opolski, śląski, małopolski, and podkarpacki. We accepted several research hypotheses which we tried to test during the research conducted. Moreover, we assumed that innovative undertakings, in individual phases of their course, require financial means whose acquiring and managing require considerable initiative from regional and local governments, but first of all from individual enterprises and financial institutions supporting this development. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 55-64